Insulin suppression of fatty acid skeletal muscle enzyme activity in postmenopausal women, and improvements in metabolic flexibility and lipoprotein lipase with aerobic exercise and weight loss - Ryan, Alice S. (Int J Obes (Lond), 2018)
BACKGROUND: Obesity and insulin resistance are characterized by metabolic inflexibility, a condition described as an inability to switch from fat oxidation during fasting to carbohydrate oxidation during hyperinsulinemia. The purpose of this study was to examine predictors of metabolic flexibility in 103 obese (37–59% fat), sedentary (VO(2)max: 19.4 ± 0.5 ml/kg/min), postmenopausal (45–76 years) women, and changes in metabolic flexibility with exercise and weight loss interventions. METHODS: Insulin sensitivity (M) and metabolic flexibility via an 80 mU/m(2)/min hyperinsulinemic–euglycemic clamp, VO(2)max, and body composition were measured. Metabolic flexibility was measured after 6-months aerobic training + weight loss (AEX + WL: n = 43) or weight loss (WL: n = 31). Basal and insulin-stimulated vastus lateralis skeletal muscle samples were available from a subset of these women (n = 45). RESULTS: Metabolic flexibility correlated inversely with glucose(120) min of OGTT, fasting insulin, and the percent change (insulin–basal) in lipoprotein lipase (LPL) activity and positively with M, but not with VO(2)max, total body fat, visceral fat, or subcutaneous abdominal fat. Skeletal muscle acyl-CoA synthase and citrate synthase activities decreased during hyperinsulinemia. Metabolic flexibility increased after AEX + WL but not WL, and the percent change in metabolic flexibility was inversely related to the percent change in insulin’s effect on LPL activity. CONCLUSION: Metabolic flexibility is related to insulin sensitivity and insulin’s action on LPL. Furthermore, metabolic flexibility and insulin suppression of skeletal muscle LPL activity increase with AEX + WL in overweight and obese, sedentary older women.